Metacognitive Skill Profiles of Chemistry Education Students in Solving Problem at Low Ability Level - Ijirana, I.; Supriadi, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
The objective of this study was to categorize and describe the behavior of chemistry education students' metacognitive skills who had a low chemical understanding (low ability) in solving problems. The findings would be the basis of data for the development of instructional design on chemistry topics by utilizing metacognitive skill aspects. The subject of this study was two first-year students of chemical education, academic year 2016/2017 that joined a basic chemistry course at the low-level ability in Universitas Tadulako. Two subjects were picked through networking using a valid test comprehension. The subjects were determined regarding the percentage of low ability which was 87% of 79 students. The profile data of metacognitive skill were obtained through an essay test, think aloud and interview. The earned data were reviewed, grouped, encoded, and examined to see its credibility employing the method and time triangulation. The research found that both students of chemistry education having a low-level of basic chemistry adopted planning skills in solving problems which were the problem identifying, goal determining, and strategy managing. However, both did not use monitoring and evaluating skills.